Pemberian Ganti Kerugian Dalam Pengadaan Tanah Untuk Pembangunan Runway 3 Bandar Udara Internasional Soekarno-Hatta - Giffron Samosir; Mr Sarjita; Koes Widarbo (Sekolah Tinggi Pertanahan Nasional, 2020)
The provision of compensation for land acquisition for the construction of runway 3 at Soekarno-Hatta International Airport found problems that made the implementation of the development not complete according to the determined target. The research objective is to determine the implementation of compensation, the problems that occur and the solutions in solving them. This research uses qualitative methods with a descriptive approach. Research results: problems in the provision of compensation, namely differences in community understanding regarding deliberations to determine compensation, objections to the amount of compensation, parties who have the right not known their whereabouts, payment of separate compensation for land and buildings that have been consigned and disputes over ownership of land acquisition objects. The settlement of the problem of giving compensation is carried out by referring to the land acquisition law, while matters that are not regulated and/or incomplete in the regulation are resolved by the policy of the land acquisition executor.